Pathogenesis of SLE Dermatitis - A Reflection of the Process in SLE Nephritis? - Fismen, Silje; Petter Rekvig, Ole; Synnøve Mortensen, Elin (Current Rheumatology Reviews, 2007)
Systemic lupus erythematosus (SLE) is an inflammatory autoimmune syndrome that may affect most organs in the body. Anti-dsDNA antibodies represent a classification criterion for SLE and are involved in lupus nephritis. Recently, the structures that bind lupus-related nephritogenic autoantibodies in vivo have been characterized by transmission electron microscopy (EM), immune-EM and co-localization immune-EM. By these methods, glomerular in vivo-bound autoantibodies were shown to co-localize with loci for binding of different experimental anti-chromatin antibodies, pointing at glomerular basement membrane-associated nucleosomes as target antigens. Lupus dermatitis has not been investigated in as much detail as lupus nephritis, but data indicate similarities between these two organ manifestations. The presence of granular antibody deposits at the dermo-epidermal junction suggests that the tissue injury is mediated by immune complexes. The deposits may be constituted by nucleosomes or chromatin and antibodies bound to them. The nucleosomes may be released locally or systemically from apoptotic cells; i.e. a process similar to that established for lupus nephritis. In this review we summarize current knowledge on immuno-pathological processes that are central in lupus nephritis, and discuss whether they may be similar to those occurring in lupus dermatitis.
Keywords: SLE